Currency Depreciation in Time of War - Whitaker, A. C. (Quarterly Journal of Economics, 1916)
I. Depreciation in general and currency depreciation, 253. — Rates of exchange and exchange values, 255. — Depreciation in the accountancy sense, 258. — Currency depreciation, in three senses, 260. — II. The practical tests of currency depreciation, 261. — III. Premium on gold, 263. — IV. Derangement of the foreign exchanges, 268. — Sterling, francs, marks, 270. — V. The behavior of prices, 273. — Indications for England, France, Germany, 276. — Summary, 278.